Development of type 2 diabetes and insulin resistance in people with HIV infection: Prevalence, incidence and associated factors. - Göran Bratt (Public Library of Science (PLoS), 2021)
Background Diabetes and insulin resistance is an emerging issue in people with HIV. HIV-related mortality and morbidities have decreased markedly over the last few decades, while co-morbidities including type 2 diabetes (T2D) have increased. Setting This study investigated the incidence of T2D and insulin resistance in a cohort of HIV-patients on effective treatment. Methods Prevalence and baseline predictors of T2D were assessed in a cohort of 570 HIV-positive patients 50 years or older. Patients without diabetes (n = 505) were followed prospectively over a median period of 7.25 year (2012-2020) until T2D development, death or end of the study. T2D was defined as repeated fasting glucose values ≥7.0 mmol/L. Insulin resistance was defined as HOMA-IR ≥3.0. Predictors of T2D development (HIV-related parameters, lipids, hypertension, central obesity, inflammation, smoking and use of statins) were assessed using logistic regression analysis. Results 30% (153/505) had insulin resistance. During follow up (3485 patient-years) 9% (43/505) developed T2D and 7% (36/505) insulin resistance. Thus, at follow up the prevalence of either T2D or insulin resistance was 46% (232/505). T2D incidence was 1.2/100 patient-years. In multivariate analysis, after adjustment for age, T2D development was associated with baseline insulin resistance, hypertriglyceridemia, central obesity and statin treatment, but no HIV-related factors. Conclusion The incidence of T2D in this cohort of patients with well controlled HIV-infection was high. The predictive factors associated with the development of T2D were not unique for HIV positive patients. The findings underline the importance of lifestyle changes in avoidance of T2D in people with HIV.